Evaluation of long‐term behaviour of composite timber‐concrete structures according to EC - Kavaliauskas, Saulius; Kvedaras, Audronis Kazimieras; Gurkšnys, Kestutis (Technological and Economic Development of Economy, 2005)
The objective of this work is the investigation of long‐term behaviour of composite timber‐concrete beams. Both ultimate and serviceability limit states have to be satisfied according to modern design codes, such as Eurocode 5. Because of the rheological phenomena such as creep, time‐dependent (viscoelastic) creep, mechano‐sorptive (moisture change) creep and shrinkage/swelling that occur in the component materials, stress and strain distribution changes in time. The rheological phenomena have to be taken into account for long term verifications. This paper presents the review of the evaluation of long term behaviour of composite timber‐concrete beams according to European design codes EC5 and EC2.Kompozitinių medienos-betono perdangų sijų ilgalaikės elgsenos vertinimas pagal euronormasSantrauka. Straipsnyje atlikta kompozitinių medienos ir betono perdangų skaičiavimo pagal Euronormas analizė, pateikti jos ilgalaikės elgsenos vertinimo aspektai. Atlikti vienos tokio tipo perdangų skaičiavimai pagal EC5 pateiktas formules – efektyvaus modulio metodą (Efective Modul Method), taikant konkrečius medienos ir betono medžiagų valkšnumo modelius.Reikšminiai žodžiai: Medienos‐betono kompozitas, ilgalaikė elgsena, valkšnumo modeliai, traukumas, ilgalaikiškumo modeliavimas.First Published Online: 21 Oct 2010